الحماية القانونية للمستهلك الإلكتروني في عقودالتجارة الإلكترونية على ضوء قانون 18-05 المتعلق بالتجارة الإلكترونية - سارة قاضي; سيف الدين ورقلي (My University, 2020)
Abstract : The issue of consumer rights and their protection isconsidered one of the most important modern marketing concepts، as itislinked to the development of the country'seconomy،especiallywith the information revolution، and in the presence of digital electronic content، and the large number of electronicadvertisementsthatchanged the concepts of luxuryneeds to benecessary in the life of the electronic consumer،where a greaterneedemerged for a study The legalframework to protect the electronic consumer rights،especiallysincemost of the countries have expressedtheirdesire and willingness to protectthis consumer،includingAlgeria،sinceitis the weak party in itsrelationshipwith the electronicresource،becauseitlacks the necessary information about the commodity or service to replace Consumption،whichmakeshim use it best for whatisachievedfor him for the purpose for whichheconcluded the contract،hence the existence of a set of protective rules in favor of the consumer،who has becomesubject to variousmethods of fraud،misinformation and deception by many commercial companies or traders in order to make a profit That isbecause the electronicprocessisconcludedfroma distance،sothat the productthatiscontractedis not in the hands of the electronic consumer، and given the greatriskinvolved in the electronicprocess in all its stages and to protect the electronic consumer from the dangers of whatheacquires of goods and services and to preventhimfromfallingvictim to the contract The electroniclaw، and on this basis، the Algerian legislatorpassed a law for the protection of the electronic consumer، to restore the balance in the consumer relationship in order to remove the harm and danger from the electronic consumer، Law No. 18-05 related to electronic commerce in general، and the protection of the electronic consumer in particular،whichisdonethrough a group of The obligations that the Algerian legislatorplaced on the electronic supplier towards the electronic consumer،imposingsome penalties in case of violatingthem، and organizing the electronicprocessbetween the two parties to the electroniccontract. ,,,,,,,,,,,,,,,,,,,,,,,,,,,,, ملخص: تعتبر مسالة حقوق المستهلك وحمايتها من أهم المفاهيم التسويقية الحديثة باعتبارها مرتبطة بتنمية إقتصاد الدول ، خاصة مع الثورة المعلوماتية ، وفي ظل وجود المحتوى الإلكتروني الرقمي، و كثرة الإعلانات الإلكترونية التي غيرت مفاهيم الحاجات الكمالية إلى ضرورية في حياة المستهلك الإلكتروني ، حيث برزت حاجة اكبر لدراسة الإطار القانون رقمي لحماية حقوق المستهلك الإلكتروني، خصوصا وان معظم الدول قد عبرت عن رغبتها واستعدادها لحماية هذا المستهلك ومنها الجزائر، كونه الطرف الضعيف في علاقته بالمورد الإلكتروني، لافتقاره المعلومات الضرورية حول السلعة أو الخدمة محل الاستهلاك ، والتي تجعله يستخدمها أفضل استخدام بما يحقق له الغرض الذي من اجله قام بإبرام العقد، ومن هنا كان لزاما وجود مجموعة من القواعد لحماية المستهلك، الذي أصبح عرضة لمختلف أساليب الغش و التضليل والخداع من قبل العديد من الشركات التجارية أو التجار بغية تحقيق الربح ، ذلك أن العملية الإلكترونية تبرم عن بعد ، بحيث لا يكون المنتج محل التعاقد بين يدي المستهلك الإلكتروني ، ونظرا للمخاطرة الكبيرة التي تنطوي عليها العملية الإلكترونية في جميع مرحلها ولوقاية المستهلك الإلكتروني من مخاطر ما يقتنيه من سلع وخدمات ولوقايته من الوقوع ضحية للعقد الإلكتروني ، وعلى هذا الأساس أقر المشرع الجزائري القانون رقم في سبيل حماية المستهلك الإلكتروني لإعادة التوازن في العلاقة الاستهلاكية بما يرفع الضرر والخطر عن المستهلك الإلكتروني ، القانون رقم 18-05 متعلق بالتجارة الإلكترونية بشكل عام ، وبحماية المستهلك الإلكتروني بشكل خاص، والتي تتم عبر مجموعة من الالتزامات التي وضعها المشرع الجزائري على عاتق المورد الإلكتروني تجاه المستهلك الإلكتروني وفرض بعض الجزاءات في حالة مخالفتها، وتنظيم العملية الإلكترونية بين طرفي العقد الإلكتروني. ,,,,,,,,,,,,,,,,,,,,,,,,,,, Résumé : La question des droits et de la protection des consommateurs est l’un des concepts de marketing modernes les plus importants car il est lié au développement de l’économie des pays de contenu numérique ", en particulier avec la révolution de l’information, et en présence de contenu électronique numérique et l’abondance de publicité électronique qui a changé les concepts des besoins de luxe nécessaires dans la vie du consommateur électronique, En particulier, la plupart des États ont exprimé leur volonté de protéger ces consommateurs, y compris l’Algérie, Être la partie faible dans sa relation avec le fournisseur électronique, faute d’informations nécessaires sur le produit ou le service soumis à la consommation ; qui lui permet d’utiliser au mieux l’objet pour lequel il a conclu le contrat et donc la nécessité d’un ensemble de règles pour la protection des consommateurs, Le processus électronique est conclu à distance, de sorte que le produit n’est pas contracté par le consommateur électronique. et compte tenu du risque élevé que comporte le processus électronique à toutes les étapes et de la protection du consommateur électronique contre le risque de son acquisition de biens et de services et de la prévention de la victime du contrat électronique, sur cette base, le législateur algérien a adopté la loi no 1 sur la protection du consommateur électronique afin de rééquilibrer la relation de consommation afin d’augmenter le préjudice et le risque pour le consommateur électronique. La loi n° 18-05 sur le commerce électronique en général, et sur la protection du consommateur électronique en particulier, impose certaines sanctions en cas de violation et réglemente le processus électronique entre les parties au contrat électronique.